1992
DOI: 10.1128/jvi.66.5.2798-2806.1992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a neuropathogenic and nonerythroleukemogenic variant of Friend murine leukemia virus PVC-211

Abstract: PVC-211 murine leukemia virus (MuLV) is a replication-competent, ecotropic type C retrovirus that was isolated after passage of the Friend virus complex through F344 rats. Unlike viruses in the Friend virus complex, it does not cause erythroleukemia but causes a rapidly progressive hind limb paralysis when injected into newborn rats and mice. We have isolated an infectious DNA clone (clone 3d) of this virus which causes neurological disease in animals as efficiently as parental PVC-211 MuLV. The restriction ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Variant PVC-211 isolated after 30 passages of Friend virus in BALB/c mice caused a rapidly progressive hind limb paralysis when injected into newborn rats and mice and displayed an expanded tropism in tissue culture. The two mutations responsible for the altered phenotype were Glu-116 to Gly and Glu-129 to Lys in the surface protein of the virus (Kai and Furuta, 1984;Masuda et al, 1992Masuda et al, , 1996aMasuda et al, , 1996b.…”
Section: B Changes In Receptor Specificity Upon Virus Evolution In Cellmentioning
confidence: 99%
“…Variant PVC-211 isolated after 30 passages of Friend virus in BALB/c mice caused a rapidly progressive hind limb paralysis when injected into newborn rats and mice and displayed an expanded tropism in tissue culture. The two mutations responsible for the altered phenotype were Glu-116 to Gly and Glu-129 to Lys in the surface protein of the virus (Kai and Furuta, 1984;Masuda et al, 1992Masuda et al, , 1996aMasuda et al, , 1996b.…”
Section: B Changes In Receptor Specificity Upon Virus Evolution In Cellmentioning
confidence: 99%
“…The primary difference between the enhancer motifs of A8 and 57 was found to be in the number of FVa motifs. The importance of FVa in causing the rapid progression of thymoma in rats was also ascertained by comparison of this region with the U3 sequence of PVC211, which has no tumorigenicity in rats (16,25). The LTR of PVC211 lacks two FVa sites compared with A8-LTR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…
Friend murine leukemia virus (FrMLV) clone A8 causes a progressive neurodegenerative disease when the virus is inoculated into newborn rats in addition to the related clones PVC211 and FB29, and of a variant, NT40, derived from FB29 (5,16,24). It has been reported that PVC211, FB29 and NT40 do not induce leukemia in rats, as they do in mice (16,17,23,25). However, clone A8 has high leukemogenic potential against both mice and rats (25).
…”
mentioning
confidence: 99%
“…Several MLV cause spongiform neurodegeneration when infected into neonatal mice or rats (1)(2)(3)(4)(5)(6)(7)(8). One common feature of these viruses, such as the neuropathogenic variant Fr-MLV A8, is that the primary determinant of the induction of neurodegenerative disease is in the env gene (9)(10)(11)(12)(13)(14)(15). The pathomechanism of spongiosis is still not well understood, but several possibilities have been proposed.…”
mentioning
confidence: 99%